Financial Management Strategies for Improving The Performance of Small and Medium Enterprises: A Case Study of Traditional Indonesian Food Outlets - Darmawan, Dhany Isnaeni; Adiyanto, Yoga; Sunaryo, Deni; Firdaus, Ahmad (Yayasan Sinergi Kawula Muda, 2025)
This study seeks to examine the impact of financial management on enhancing the performance of Micro, Small, and Medium Enterprises (MSMEs), particularly in traditional Indonesian food outlets. Data were gathered through direct observation of these MSMEs using primary sources. The research adopts an action research approach with a case study method. Data collection techniques included interviews, observations, and documentation. The analysis used Multiple Linear Regression, Classical Assumption Testing, and Hypothesis Testing with SPSS software. The findings reveal that financial planning, financial record-keeping, and the separation of personal and business finances have a significant and positive effect on the performance of MSMEs. The R-Square (R²) value of 0.825 indicates that these independent variables can explain 82.5% of MSME performance variation, while the remaining 17.5% is attributed to other factors not explored in this study. The practical implications of this research suggest that traditional Indonesian food MSMEs should emphasize structured financial planning, accurate financial record-keeping, and precise separation of personal and business finances. These practices will enable MSMEs to assess their performance better and make informed business decisions. The study recommends that MSMEs adopt sound financial planning practices, maintain precise financial records, and consistently separate personal from business finances. By doing so, MSMEs can improve their financial management, enhancing business performance and sustainability.